1992
DOI: 10.1073/pnas.89.18.8462
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling and episodic secretion of gonadotropin-releasing hormone in hypothalamic neurons.

Abstract: Gonadotropin-releasing hormone (GnRH) is released episodically into the pituitary portal vessels and from hypothalamic tissue of male and female rats in vitro. Perfused primary cultures of rat hypothalamic neurons, as well as the GT1-1 GnRH neuronal cell line, spontaneously exhibited episodic GnRH secretion of comparable frequency to that observed with perifused hypothalami. Such pulsatile GnRH release from GT1 cells indicates that GnRH neurons generate rhythmic secretory activity in the absence of input from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
141
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 36 publications
7
141
3
Order By: Relevance
“…This concept of differential coupling of specific channels to different rates of transmitter or hormone release could be also applied to other cell types (44). L-type channels have been also involved in the secretion of gonadotropin-releasing hormone (GnRH) by perifused primary cultures of rat hypothalamic neurons (45). Indeed, some neurons secrete two kinds of neuromediators: (i) fast acting neurotransmitters, such as biogenic amines, acetylcholine, glutamate, GABA or glycine, and (ii) neuropeptides, such as GnRH, neuropeptide Y, substance P, vasoactive intestinal peptide, somatostatin or AngII.…”
Section: L-type Channel-mediated Secretionmentioning
confidence: 99%
“…This concept of differential coupling of specific channels to different rates of transmitter or hormone release could be also applied to other cell types (44). L-type channels have been also involved in the secretion of gonadotropin-releasing hormone (GnRH) by perifused primary cultures of rat hypothalamic neurons (45). Indeed, some neurons secrete two kinds of neuromediators: (i) fast acting neurotransmitters, such as biogenic amines, acetylcholine, glutamate, GABA or glycine, and (ii) neuropeptides, such as GnRH, neuropeptide Y, substance P, vasoactive intestinal peptide, somatostatin or AngII.…”
Section: L-type Channel-mediated Secretionmentioning
confidence: 99%
“…Further complicating the understanding of these questions is the complexity of the neural connectivity of GnRH neurons. The development of the highly differentiated GT1 GnRH neuronal cell lines (1) and the demonstration that pulsatile release was an intrinsic property of the cells provided a model to study molecular events underlying pulsatile GnRH release (2)(3)(4). However, one is always faced with the problem of translating findings from an immortalized cell line to the physiological setting.…”
mentioning
confidence: 99%
“…The cells are highly differentiated and express and process GnRH at high levels (1,2). The pulsatile release of GnRH appears to be an intrinsic property of individual or networks of GnRH neurons, since cultures of the GT1 cells release GnRH with a pulse frequency identical to that seen in castrate rodents (3)(4)(5). In vivo numerous efferent inputs to GnRH neurons release neurotransmitters that stimulate GnRH secretion (6).…”
mentioning
confidence: 99%
“…The level of secretion of GnRH was proportional to the activation of AC and increases in cAMP levels. These data are all consistent with the hypothesis that the stimulation of AC results in the increased formation of cAMP, activating the signaling cascade responsible for stimulation of GnRH release.Several studies have shown that depolarization followed by the influx of extracellular Ca 2ϩ via voltage-dependent Ca 2ϩ channels is essential for the stimulation of GnRH secretion from GT1 cells (5,13,14). Stimulation of GnRH secretion from GT1 cells by NE was correlated with depolarization of the cells and the influx of extracellular Ca 2ϩ (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation